Metodología basada en proyectos en la asignatura de Ciencias Naturales - Asimbaya Chacha, Leslee Jomaira (2023)
This investigative work is mainly based on applying methodologies based on projects in the subject of natural sciences. It exhibits its theoretical foundation, which covers topics related to the object of study such as the project-based strategy for teaching - learning of natural sciences. The qualitative research methodology, the inductive, empirical method and a bibliographic and field research were raised. The technique applied was observation and the instrument to be used was the observation guide that allows to demonstrate the teacher's performance during the development of the natural sciences class, to obtain information from the research subjects for the elaboration of resources. The investigative work is based on a representative population of the Juan Abel Echeverría Educational Unit of the city of Latacunga, who is considered as the main actors of the investigative process a teacher and thirty-seven students, the same ones who were participants in the observation of the class. . In the same way, Project-Based Learning (ABP) strategies are designed through demonstrative classes to strengthen the teaching-learning process in the area of Natural Sciences of the Juan Abel Echeverría Educational Unit. Finally, it contributed with the elaboration of didactic resources that served to develop the learning of the students, allowing to strengthen the knowledge in the area of Natural Sciences.